Traumatic infratentorial epidural haematoma: presentation and treatment outcome at the Jos University Teaching Hospital, North Central Nigeria - Shilong, Danaan J.; Bot, Gyang M. (International Journal of Research in Medical Sciences, 2021)
Background: Traumatic infratentorial epidural haematoma (TIEH), also called posterior fossa epidural haematomas when compared to their supratentorial counterparts, are very rare and their presentation nonspecific, accounting for 0.1-0.3% of all head trauma. Data on TIEH in our environment is very scanty. Our objective was to document the different presentations of TIEH and the outcome of management of these patients in our setting. Methods: This was a retrospective study of consecutive patients with head injury in whom non contrast cranial CT scan showed the presence of an infratentorial epidural haematoma and who presented to the Jos university teaching hospital between January 2012 to December 2020. The patients’ demographics, aetiology, clinical features, CT scan findings and outcome of treatment were extracted from the case folders and analysed using simple proportions. Results: There was a total of seven patients with TIEH out of a total of 308 patients with traumatic epidural haematoma, thus accounting for 2.3% of epidural haematomas in our series. All the TIEH were caused by road traffic collisions, all but one (85.7%) occurred in adults. Six (85.7%) of the patients had occipital skull fractures detected with cranial CT scan or at surgery. Two (28.6%) of the patients were managed non-operatively under close monitoring and did well. Five (71.4%) of the patients were managed surgically. There was one death, giving an overall mortality of (14.3%). Conclusions: TIEH is rare, the presentation is non-specific and early surgical decompression is lifesaving in selected patients.